2010
DOI: 10.1303/aez.2010.207
|View full text |Cite
|
Sign up to set email alerts
|

Circular yellow sticky trap with black background enhances attraction of Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae)

Abstract: Yellow sticky flat traps were cut into six geometrical shapes (square, circle, semi-circle, diamond, triangle, and inverted triangle) to evaluate their attractiveness to Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae). The square was used as a standard to compare with other shapes in the laboratory. Circle was the most effective, attracting 2.7 and 1.5 times more thrips in choice and no-choice experiments, respectively. Four different background colors were also employed in the circular trap, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 19 publications
2
35
0
3
Order By: Relevance
“…5. Insects that are attracted to these yellowish devices include important crop pests such as planthoppers, leafhoppers, aphids, whiteflies, thrips, and leafminer flies (Esker et al 2004;Mainali and Lim 2010;Vaishampayan et al 1975). Yellow sticky plates or rolls have become important tools for the physical control of these pests (Tokumaru et al 2009): those in use at a tomato cultivation facility are shown in Fig.…”
Section: Attraction Of Insects To Light Sources At Nightmentioning
confidence: 99%
“…5. Insects that are attracted to these yellowish devices include important crop pests such as planthoppers, leafhoppers, aphids, whiteflies, thrips, and leafminer flies (Esker et al 2004;Mainali and Lim 2010;Vaishampayan et al 1975). Yellow sticky plates or rolls have become important tools for the physical control of these pests (Tokumaru et al 2009): those in use at a tomato cultivation facility are shown in Fig.…”
Section: Attraction Of Insects To Light Sources At Nightmentioning
confidence: 99%
“…These two colors are commonly used for traps to catch several insect pests (e.g., Harman et al 2007;Gu et al 2008;Mainali and Lim 2010). Each colored sticky sheet (26 9 10 cm) (Horiver, Arysta LifeScience, Tokyo, Japan) was fixed with props and installed in a forage maize so that the top of the sticky sheet was located at a 40-cm height from the ground (Fig.…”
Section: Examination Of the Color Attractiveness For Insectsmentioning
confidence: 99%
“…The use of colour cues by insects has been studied intensely. Most commonly, insects seem to have a preference for broadband colours that appear yellow to humans (Prokopy and Owens, 1983;Mainali and Lim, 2010;de Oliveira et al, 2015) and are believed to represent a super-normal foliage-type stimulus for herbivores (Prokopy, 1972). Many pollinators, on the other hand, have an innate preference for blue (Kelber, 1997;Raine and Chittka, 2005;Burger et al, 2010;Yoshida et al, 2015).…”
Section: Introductionmentioning
confidence: 99%